P-131 Information with impact: analysis of feedback about what to expect at end of life online information. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Evans, Amy; Bonnar, Kim; Masterton, Morven
Abstract : Background: The Ambitions for Palliative and End of Life Care framework highlights the importance of information in supporting people affected by death and dying (National Palliative and End of Life Care Partnership, 2015). All information should meet high standards. Ensuring users can provide feedback is a core principle of the NHS Information Standard. Aim: A national charity sought feedback on its What to expect at end of life online information. The aim was to assess the usefulness of the information and to understand what worked, possible improvements, and any impact the information had on end of life experiences. Method: In March 2019 a survey was embedded on three web pages, which included two questions: How useful did you find this page? Please tell us why. Results: 106 responses were received. 88% found the pages either Very useful (74%) or Useful (14%). Thematic analysis of the open text boxes identified these themes: Informative; Helped them prepare for future; Easy to understand; Sensitive/compassionate; Confidence/reassurance about actions. The qualitative open text boxes provided examples of the impact the information can have, including: 'Having some idea of the indications of imminent death will help us to organise our time to ensure we're there when his time is approaching.' 'Although the situation is harrowing, I think part of the anxiety comes from fear of the unknown. This diminishes when we have the small comfort, of knowing what to expect.' Six respondents felt there were gaps in the content, including how to deal with emotions. Conclusion: This research tells us that most respondents found the information useful, and that it has the potential to positively impact on people's end of life experiences.